Women’s role in Uzbek society and their empowerment - Nazirova, Sayyora (My University, 2025)
Bu çalışma, kadınların Özbek toplumundaki tarihsel, sosyal ve politik rollerinin dönüşümünü incelemektedir. Tarihsel analizler ve Özbekistan’ın farklı bölgelerinde yürütülen saha araştırmalarına dayanan tez, kadınların geçmişten günümüze yaşadığı deneyimleri çok boyutlu bir perspektifle ele almaktadır. Tez, kadınların geleneksel toplumsal rollerle şekillenen tarihsel konumlarını ve Sovyet döneminin bu rollere getirdiği dönüşümleri analiz ederek başlamaktadır. Sovyet sonrası geçiş sürecinde kadınların karşılaştığı zorluklar ve elde ettikleri fırsatlar detaylı biçimde incelenmekte; özellikle eğitim, istihdam, siyasi katılım, aile hayatı ve ekonomik faaliyetlerdeki güncel durumları değerlendirilmektedir. Saha araştırmaları aracılığıyla kadınların bireysel deneyimlerine odaklanan çalışma, hem karşılaştıkları cinsiyet temelli eşitsizlikleri hem de sergiledikleri direniş ve özneleşme pratiklerini ortaya koymaktadır. Bulgular, kadınların toplumsal cinsiyet eşitliği ve güçlenme mücadelesinde gösterdikleri kararlılığı gözler önüne sermektedir. Son olarak, tez kadınların sosyal statülerini iyileştirmeye, toplumsal cinsiyet eşitliğini teşvik etmeye ve onları güçlendirmeye yönelik somut politika önerileri sunmaktadır. Bu öneriler; eğitim reformları, ekonomik fırsatların artırılması, yasa ve politika değişiklikleri ile toplumsal farkındalık kampanyalarını kapsamaktadır. Böylece, daha kapsayıcı ve eşitlikçi bir toplum inşası yolunda Özbek kadınlarının potansiyelinden tam anlamıyla yararlanılması hedeflenmektedir

This thesis examines the development of role of women in Uzbek society, exploring their historical experiences, current status, and ongoing struggles for empowerment. Drawing upon historical analysis and field research, the study provides a multifaceted understanding of the social, cultural, political, and economic factors that have shaped women's lives in Uzbekistan. The study begins by tracing the history of experiences and roles of women in Uzbek society, highlighting the traditional expectations and impositions placed upon them in history and the transformative impact of the Soviet era. It then delves into the challenges and opportunities women faced during the post-Soviet transition and analyzes their current status in education, employment, political participation, family life, and economic activity. Through semi-structured interviews conducted across diverse regions of Uzbekistan, the thesis sheds light on the lived experiences of women and the complex realities they navigate. The findings indicate the persistent gender inequalities and discriminatory practices they encounter, while also showcasing their resilience, agency, and ongoing efforts to achieve greater agency and equality. Based on empirical findings, the thesis concludes by offering recommendations how to improve social status and places of women, promote gender equality and empower women in Uzbek society. These recommendations address key areas such as policy changes, educational reforms, economic opportunities, and social awareness campaigns. By fostering a more inclusive and equitable environment, Uzbekistan can harness the full potential of its women and contribute to a more just and prosperous future.
Keywords: Aile Hayatı; Education; Eğitim; Employment; Empowerment; Family Life; Field Research; Gender Equality; Güçlendirme; Historical Analysis; İstihdam; Kadına Yönelik Şiddet; Kadınlar; Özbekistan; Policy Recommendations; Political Participation; Politika Önerileri Women; Saha Araştırması; Siyasi Katılım; Social conditions; Sosyal durum; Tarihsel Analiz; Toplumsal Cinsiyet Eşitliği; Uzbekistan; Violence Against Women; Women